Analisis Data Panel Pengaruh PDRB, BI Rate dan IPM Terhadap Tabungan Bank - Muhammad Arfan Harahap; Muhammad Hafizh; Anjur Perkasa Alam (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
Savings play an important role in improving the national and regional economy. This study aims to analyze the effect of PDRB, BI Rate and IPM on savings at the Bank either partially or simultaneously. Panel data analysis was used for data in North Sumatra Province with identical research variables. The use of secondary data in this study is based ondata time series and cross section from 2010-2020. In addition, to see the effect of specific research variables in Langkat Regency, multiple linear regression models are used. The data was processed with the help of the eviews version 11 program and passed the classic assumption problem test and the data normality test. The initial findings in this study are that the IPM variable has a significant effect on savings at banks in North Sumatra, while the BI Rate and PDRB variables have no effect on savings, but at a significance level of 10%, the BI Rate variable has an effect. Further findings are that there is a significant effect of the PDRB and IPM variables on public savings in Langkat Regency. Meanwhile, the BI Rate variable has no effect on the Langkat Regency community savings. Simultaneously all independent variables of the study affect the dependent variable.